The Geographic Revolution in Early America : Maps, Literacy, and National Identity - Brückner, Martin, 1963- (Book collections on Project MUSE., 2006)
The rapid rise in popularity of maps and geography handbooks in the eighteenth century ushered in a new geographic literacy among non elite Americans. This illustrated book argues that geographic literacy as it was played out in popular literary genres significantly influenced the formation of identity in America from the 1680s to the 1820s.